Analysis of Giving Credit to Liquidity of the South Sulawesi Regional Development Bank Bantaeng District Branch - Sulfianti, Anna (Universitas Negeri Makassar, 2019)
This study examines the relationship between granting with a liquid level in a bank that aims: (1) To determine the extent to which credit is given to the liquidity position of the South Sulawesi Regional Development Bank. (2) To get a clear picture of the relationship between the amount of funds available and the credit activities of the South Sulawesi Regional Development bank. (3) To find out the policies stipulated by the Regional Development Bank of South Sulawesi, especially the credit sector. The data collection method used in this study, is through Library Research, and Field Research. Based on the analysis of the results of the research and discussion, in this section it can be concluded: (1) the South Sulawesi Regional Development Bank which is the Regional Government of South Sulawesi Province in addition to functioning as a public bank as well as regional government holders whose source of funds comes from local governments and service office located in the province of South Sulawesi. (2) The development of credit funds channeled by the Regional Development Banks of South Sulawesi tends to increase from year to year, (3) From the supply of funds and credit channeled by the Regional Development Bank of South Sulawesi, it is known that the supply of these funds is not channeled as credit, either short-term credit and long-term credit.